Differential barrier and corridor effects of power lines, roads and rivers on moose (Alces alces) movements. Issue 4 (24th April 2015) - Bartzke, G. S.; May, R.; Solberg, E. J.; Rolandsen, C. M.; Røskaft, E.
Abstract : Building new power lines is required to satisfy increasing demands for the transmission of electricity, and at the same time the road network is expanding. To provide guidelines for the routing of new power lines and roads, it is essential to test whether linear features deter or attract movements of animals in different landscape settings. Using GPS relocation data from 151 moose ( Alces alces L.) in central Norway, we tested for barrier and corridor effects of roads, power lines and rivers and accounted for forest cover, the topographical orientation of linear features and the placement of other nearby linear features. We predicted step selection probabilities for different movement options at varying distances from linear features and linear feature combinations. Barrier and corridor effects of linear features altered moose movements, although effects were minor compared to the effects of topography and forest cover. Moose did not avoid crossing power lines, unless the placement of power lines along contour lines impeded movements across them. In contrast, moose avoided crossing of roads and rivers in forests. Moose more likely moved along linear features when getting closer to linear features. Barrier and corridor effects were higher for road/river combinations compared to single linear features. Likewise, the barrier and corridor effects were higher for road/power line combinations, but not power line/river combinations compared to single linear features, when moose were close to the edge of those features. The inconsistent pattern could be due to the low sample size. We found indications of higher disturbance potential of roads compared to power lines and rivers. Managing vegetation in power line rights‐of‐way to provide abundant browse could counteract possible disturbance, while wildlife overpasses could mitigate road fragmentation effects.